Characteristics of superior orbital subperiosteal abscesses in children. (12th June 2016) - Quintanilla‐Dieck, Lourdes; Chinnadurai, Sivakumar; Goudy, Steven L.; Virgin, Frank W.
Abstract : Objectives/Hypothesis: Superior pediatric orbital subperiosteal abscesses (SPAs) are less common than medial ones, and clinical features specific to patients with superior SPAs have not been well defined. Clinical characteristics between patients with superior and medial SPAs are compared to determine whether superior location is a risk factor for surgical intervention. Study Design: Retrospective cohort study. Methods: The target population consisted of patients diagnosed with an SPA and seen by the pediatric otolaryngology service at a tertiary children's hospital between January 2010 and October 2014. Imaging characteristics including proptosis, hypoglobus, intraorbital air, and abscess volume as well as treatment interventions were reviewed. Results: Forty patients between 5 and 17 years of age treated for an orbital SPA were identified. Thirteen patients were identified as having superior SPAs; 27 had medial SPAs. The average ages in the two groups were 10.92 and 9.26 years, respectively. The odds ratio for surgical treatment per each increasing year of age was 1.5 ( P = .004). The proportion of patients requiring surgery was significantly different between the groups (12/13 superior vs. 13/27 medial, P = .01). The predominant organism group cultured in surgical patients was Streptococcus anginosus (8/24, 29.17%). Superior SPA patients had significantly more proptosis, hypoglobus, and abscess volume on computed tomography scan. Conclusions: Patients with superior SPAs may present with more advanced disease, leading to a higher rate of characteristics such as proptosis, hypoglobus, and intraorbital air, factors that would predispose to surgical drainage. We found that abscess volume was the most predictive of surgery. Level of Evidence: 4 Laryngoscope, 127:735–740, 2017